Окно, открытое настежь...: историческая литература / А. А. Артамонов - Артамонов Альфред Александрович (Удмуртия, 2008)
Экземпляры: (20170705) / Инвентарный номер: 34386 / Цена: 150.00 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: А 86 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)я9